Translation and Cultural Adaptation of the StimQ for Use with Italian Children from Kindergartens - Roberta De Salve; Sara Romanelli; Francesco Frontani; Francesca Policastro; Anna Berardi; Donatella Valente; Giovanni Galeoto (MDPI AG, 2023)
The StimQ questionnaire is used to assess the home environment of children. The questionnaire is comprised of four subscales, and it was completed by the main caregiver. The items were different considering the band ages of the children: infants (5-12 months), toddlers (12-36 months), and preschoolers (36-72 months). The aim of the study was to translate, transculturally adapt, and evaluate the psychometric characteristics of the Italian version of the StimQ. To achieve this goal, a sample of 142 children was recruited from different kindergartens. The mean age of the group was 30.63 (SD 19.56), and 112 of them were female. The main caregiver was the mother in 95% of the cases. The Cronbach's alfa was excellent, considering the total score (0.82 for infants, 0.85 for toddlers, and 0.86 for preschoolers). Intrarater reliability was performed by administering the questionnaire after 48 h and by two different researchers. Both analyses showed an excellent reliability for the total score and all the subscales. The intrarater reliability was 0.99 for the infant, 1 for the toddler and 0.99 for the preschooler age groups. The interrater reliability was 0.95 for the infant, 0.93 for the toddler, and 0.97 for the preschooler age groups. The StimQ is a reliable questionnaire that could be helpful for clinicians and researchers who work with children in Italy.